Effects of sex on imaging-based intravenous thrombolysis for ischaemic stroke with unknown onset time: a pooled analysis of clinical trials - Fukuda-Doi, Mayumi; Hacke, Werner; Ringleb, Peter A.; Toyoda, Kazunori (European stroke journal, 2025)
Introduction: The effects of imaging-based intravenous thrombolysis on outcomes based on patient sex remain unclear. We aimed to investigate whether outcomes among patients with stroke with an unknown onset time and treated with imaging-based intravenous thrombolysis are influenced by their sex. Patients and methods: This study was a pooled analysis of individual patient-level data acquired from the Evaluation of unknown Onset Stroke thrombolysis trials. Patients treated with imaging-based intravenous thrombolysis for stroke with an unknown onset time were included. The primary outcome was a favourable outcome (modified Rankin Scale score 0-1) at 90 days. The sex-based difference in outcomes was studied using mixed-effect logistic or ordinal regression models, considering potential heterogeneity across trials. Results: Out of 509 patients in total, 204 (40.1%) were women. Compared with men, women were older and more likely to have atrial fibrillation. Baseline National Institutes of Health Stroke Scale score was higher and hours from last-known-well to treatment were longer for women than for men. Favourable outcomes occurred less often among women than among men. However, multivariate adjustment revealed a non-significant association between female sex and favourable outcome (adjusted odds ratio: 1.04 [95% confidence interval: 0.66-1.52], p = 0.98). Discussion and conclusion: Pooled data from the included clinical trials showed that women with ischaemic stroke with an unknown onset time had worse functional outcomes following imaging-based intravenous thrombolysis than did men. However, this sex-based difference can be explained by the higher age and more severe clinical status at onset among women.
Online veröffentlicht: 3. Januar 2025
Gesehen am 17.10.2025